Growing up in Australia: The Longitudinal Study of Australian Children is now walking and talking - Smart, D; Gray, M (My University, 2008)
This edition of Family Matters focuses on the work of Growing Up in Australia: the Longitudinal Study of Australian Children (LSAC), which is managed by the Australian Institute of Family Studies and was initiated by the Federal Government's Department of Families, Housing, Community Services and Indigenous Affairs. LSAC is now into Wave 2, and the articles in this edition illustrate the range of topics that can be investigated with longitudinal data on child development. This introductory article summarises the edition, and presents an overview of LSAC, including its study design and sample, and the 14 key research questions which guide the study.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology